2021
DOI: 10.3389/fgwh.2021.764693
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Challenges in Endometriosis Pain Communication Between Patients and Doctors: The Role of Language

Abstract: Introduction: In the context of the complex medical, social, and economic factors that contribute to endometriosis diagnosis delay and its consequent impact on quality of life, this report focuses on patient-practitioner pain communication and examines the role of language in doctor-patient communication. Our study explored what patients and doctors consider challenging and effective in endometriosis pain communication. It further examined what commonly used metaphors by patients could be suggestive, or not, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The other was the seventh result in the endometriosis search for the Women's Health review, which was a hint to a recently completed study which had not yet been published 21 . Following correspondence with the authors we ascertained that the study was due publication in journal article format during the period that the review would be undertaken, and thus was included in the review later in the review process 22 . Although the occupational health review Google Search searches were re‐run 11 months after the initial searches for the purposes of this analysis, we did not identify any previously unidentified relevant studies for the occupational health review which were not also identifiable by the bibliographic database searches, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The other was the seventh result in the endometriosis search for the Women's Health review, which was a hint to a recently completed study which had not yet been published 21 . Following correspondence with the authors we ascertained that the study was due publication in journal article format during the period that the review would be undertaken, and thus was included in the review later in the review process 22 . Although the occupational health review Google Search searches were re‐run 11 months after the initial searches for the purposes of this analysis, we did not identify any previously unidentified relevant studies for the occupational health review which were not also identifiable by the bibliographic database searches, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported that a proportion of participants had a special interest in gynaecology, which in some studies was achieved through purposive sampling. 17 , 29 , 41 , 43 Other studies used purposive sampling to recruit participants who are routinely exposed to populations or diseases of interest. 30 32 , 35 , 37 , 40 This sometimes meant that more female than male participants were included.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five papers published 1998-2023 were included (14-18, 27-46) (see Table 2 and Supplementary Table S3). Four studies reported that a proportion of participants had a special interest in gynaecology, which in some studies was achieved through purposive sampling (17,30,42,44). Other studies used purposive sampling to recruit participants who are routinely exposed to populations or diseases of interest (31-33, 36, 38, 41).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the need for an interdisciplinary approach to pain, throughout Western medicine it is still common for many practitioners to use the “pain scale” in clinical practice, where patients are asked to label their pain on a scale quantitatively from 1 to 10. This tool has been critiqued for its subjectivity and, although other alternatives exist, they are not as commonly practiced ( 62 , 63 ). Despite the prevalence of chronic pain and illnesses, people living with them are likely to experience disbelief and invalidation from their practitioners, which can cause isolation, depression, and emotional distress ( 64 , 65 ).…”
Section: Discussionmentioning
confidence: 99%